Accelerating Trade and Integration in the Caribbean : Policy Options for Sustained Growth, Job Creation, and Poverty Reduction - Hamilton, Pamela Coke; Tsikata, Yvonne; Moreira, Emmanuel Pinto (World Bank, 2012)
This volume builds on the foundation laid by the 2005 report by focusing on the factors affecting the region's competitiveness and the critical role that the Caribbean Single Market and Economy (CSME) has to play as a driver of integration and economic development. In addition it highlights the potential of the Economic Partnership Agreement (EPA), if properly implemented, to significantly increase the region's competitiveness and to help it attain long-term sustained development. This potential, however, will only be realized if precise trade and competitiveness strategies are crafted to focus primarily on removing the constraints to competitiveness endemic in the region. In addition, and this is a critical element of any newly-devised strategy, is the necessity to revise regional institutional mechanisms and mandates to promote implementation and to take advantage of the market access opportunities presented by successive trade agreements such as the EPA. This report, while highlighting the need for immediate and concrete actions on the part of the Caribbean Community (CARICOM) member states, also recognizes the responsibility of the donor community in helping to play a catalytic role in supporting trade reform and macroeconomic stability. The aid for trade agenda must seek to address the weaknesses inherent in the formulation and application of international aid policies and implement new frameworks aimed at enhancing the ability of these small nation states to meet and overcome the challenges of global competitiveness.